Platelet aggregation values in patients with cardiovascular risk factors are reduced by verbascoside treatment. A randomized study. (July 2015) - Campo, Gianluca; Pavasini, Rita; Biscaglia, Simone; Ferri, Alessandra; Andrenacci, Elisa; Tebaldi, Matteo; Ferrari, Roberto
Graphical abstract: Abstract: Verbascoside, a phenolic compound, showed several favorable biological activities, including an antiplatelet activity. No in vivo studies tested its efficacy and safety in subjects with cardiovascular (CV) factors. The aim of this randomized, single-center, double-blind, phase II study was to assess the efficacy and tolerability of verbascoside intake for the modulation of platelet aggregation (PA) values in subjects with cardiovascular (CV) risk factors. One-hundred subjects with at least one CV risk factor (age >65 years, diabetes mellitus, hypertension, current cigarettes use, hyperlidemia, waist circumference >102 cm in male or >88 cm in female) were enrolled and randomly assigned to receive placebo or verbascoside 50 mg or verbascoside 100 mg. PA was measured at baseline and after 2 weeks of study drug assumption, with light transmittance aggregometry (arachidonic acid, AA, 1 μM and adenosine diphosphate, ADP, 5 μM). Two weeks of treatment with placebo or verbascoside 50 mg did not modify PA values (both after AA and ADP stimuli). On the contrary, after 2 weeks of verbascoside 100 mg, PA values decreased significantly (from 51 ± 13% to 39 ± 15%, p  < 0.01 after AA; from 60 ± 12% to 49 ± 15%, p  = 0.01 after ADP). No serious adverse events were reported during the study, and no subjects discontinued the study because of adverse events. We conclude that long-term intake of verbascoside 100 mg significantly reduces PA values in subjects with CV risk factors.